Activity Test Ni/ZrO2-SiO2 Catalyst for Hydrodeoxygenation Reactions Mixtures the Furfurylidene Acetone Compound (FAc) and Difurfurylidene Acetone (F2Ac) - Dita Prihartini; Siti Mariyah Ulfa; Elvina Dhiaul Iftitah (Natural B, Journal of Health and Environmental Sciences, 2016)
Hydrodeoxygenation (HDO) reaction of furfural derivatives have widely studied because these reaction produce saturated alkane which potensial for renewable fuels. Nickel based catalyst impregnated in to ZrO2-SiO2 (Ni/ZrO2-SiO2) was prepared and its activity is evaluated for HDO of furfurilidene aceto (FAc) and difurfurilidene acetone (F2Ac). Ni/ZrO2-SiO2 catalys was prepared from Ni(NO3)2.6H2O with 10% Ni loading over ZrO2-SiO2 by wet impregnation method. Characterization using X-ray showed the diffraction of Ni detected at 2θ = 44.42, 51.73, and 76.26. Catalyst activity for HDO of FAc and F2Ac was carried out at 200oC for 2 hours in batch system. According to gas chromatography analysis, the conversion of product is 100% with selectivity for 2-octanol and dodeka-6-ene is 88,22% and 2,99%, respectively.